A novel strategy for emergency treatment of coronary perforations by placing a drug-eluting stent before sealing off the leakage with a covered stent to improve long-term outcomes in patients with coronary artery perforations - Ayoub, Mohamed; Corpataux, Noé; Tajti, Péter; Behnes, Michael; Schupp, Tobias; Forner, Jan; Akın, Ibrahim; Westermann, Dirk; Rudolph, Volker; Mashayekhi, Kambis (Journal of Personalized Medicine, 2023)
We aimed to investigate the safety, feasibility, and long-term results of drug-eluting stent implantation before covered stents for treating coronary artery perforation (CAP). Between 2015 and 2020, 12,733 patients undergoing percutaneous coronary intervention (PCI) were retrospectively analyzed. The primary endpoint was 1-year target lesion revascularization (TLR), whereas secondary endpoints included the rate of major adverse cardiac and cerebrovascular events (MACCE) and all-cause death at 1 year. A total of 159 patients with CAP were identified during the study period, of whom 47.2% (n = 75) were treated with a covered stent (CS group) because of complex and/or severe CAP and 84 (52.8%) without (non-CS group). In the majority of patients, emergency drug-eluting stent placement before covered stent implantation was feasible (n = 69, 82%). There were no significant differences among patients treated with or without a covered stent in terms of primary or secondary clinical endpoints: a similar rate of TLR (18.67% vs. 21.43%, p = 0.6646), MACCE (25.33% vs. 22.62%, p = 0.6887), and 1-year mortality (12.00% vs. 11.90%, p = 0.9853) were identified comparing cases with covered stent implantation and without. In conclusion, our study implicates that the use of covered stents for sealing coronary perforation might not impact the 1-year clinical outcome if used properly. Moreover, the emergent use of drug-eluting stents before covered stent implantation in CAP is a safe and effective method to avoid target lesion revascularization in patients treated with covered stents.
Gesehen am 16.05.2024